A Clinical Analysis and Literature Review of Six Cases with Primary Pulmonary Lymphoepithelioma-Like Carcinoma. (29th April 2022) - Ye, Lingyan; Luo, Dinghai; Li, Haiyan; Zheng, Haihong; He, Susu; Lin, Ling; Fang, Yicheng; Ye, Junhui; Chen, Chengshui
Abstract : Object . To investigate the clinicopathological features, imaging findings, treatment, and prognosis of primary pulmonary lymphoepitheliomatoid-like carcinoma. Methods . The clinical data of six patients with primary pulmonary lymphoepithelioma-like carcinoma treated in Zhejiang Taizhou Hospital of Taizhou Enze Medical Center (Group) from May 2014 to December 2018 were summarized and analyzed. Combined with the relevant literature, the primary pulmonary lymphoepithelioma-like carcinoma was analyzed retrospectively. Results . The main manifestations of six patients were respiratory symptoms, and cough was the most common. The imaging features of six patients were mainly round-like high-density mass shadow or nodule shadow. All patients were diagnosed by pathology. Microscopically, the cancer cells were nested, with large nuclei and vacuoles and abundant lymphocyte infiltration in the tumor stroma. The positive rates of EBER, p63, CK5/6, and Ki-67 were high, and TTF-1 was negative. Five patients received surgical treatment. One patient developed brain metastasis 12 months after operation and received craniocerebral radiotherapy. The other patients did not receive radiotherapy and chemotherapy, and one patient did not receive treatment. After follow-up, four patients survived so far, the longest survival time was 82 months, one patient lost follow-up, and one patient died of lung metastasis 24 months after operation. Conclusion . Primary pulmonary lymphoepitheliomatoid-like carcinoma is a rare lung malignant tumor, whose pathogenesis is related to Epstein-Barr virus infection. The clinical manifestations are nonspecific, but with unique pathological characteristics. Surgical resection is the proper treatment for early-stage patients, and comprehensive treatment with surgery as the main treatment is suitable for late-stage patients. The prognosis is good.